A history of Belize nation in the making - Leslie, Robert; Heusner, Rachel (Explorer, 2016)
"A History of Belize, Nation in the Making traces the history of our country. It focusses [sic] on how we became what we are today. It travels through time and gives us the opportunity to study the complex society which we have inherited. History is never complete for we create history each day. The people, places and events presented in this book show us how important history is to a nation. We cannot move constructively into the future unless we understand the past and benefit from that knowledge. This book helps us to do just that.''--Page 4 of cover